1999
DOI: 10.1143/jpsj.68.1496
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Surface and Band Dispersion in La2-xSrxCuO4

Abstract: Using angle-resolved photoemission spectroscopy (ARPES), we observe the band structure, the Fermi surface and their doping dependences in La2−xSrxCuO4. The results reveal that the Fermi surface undergoes a dramatic change: it is holelike and centered at (π,π) in underdoped (x = 0.1) and optimally doped (x = 0.15) samples as in other cuprates, while it is electronlike and centered at (0,0) in heavily overdoped (x = 0.3) ones. The peak in the ARPES spectra near (π/2,π/2) is broad and weak unlike that in other cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
130
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 37 publications
39
130
2
Order By: Relevance
“…Recent analysis of angle-resolved photoemission spectroscopy data has shown that both t N N N and t nN N N are necessary for understanding the dispersion and line shape of the spectral function in the t-J model [26]. Tohyama et al [25] have estimated the ratio t N N N /t N N and t nN N N /t N N to be -0.12 and 0.08, respectively, by fitting the tight-binding Fermi surface to the experimental one in the overdoped sample [47] on the assumption that in the overdoped region the Fermi surface of the tight-binding band is the same as that of the t-t'-t"-J model. The values here-proposed are in good agreement with these ratio: (ii) the singlet displacement operator h SD has to be taken into account, at least for the colinear displacement, since h SD ≃ -80 meV.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of angle-resolved photoemission spectroscopy data has shown that both t N N N and t nN N N are necessary for understanding the dispersion and line shape of the spectral function in the t-J model [26]. Tohyama et al [25] have estimated the ratio t N N N /t N N and t nN N N /t N N to be -0.12 and 0.08, respectively, by fitting the tight-binding Fermi surface to the experimental one in the overdoped sample [47] on the assumption that in the overdoped region the Fermi surface of the tight-binding band is the same as that of the t-t'-t"-J model. The values here-proposed are in good agreement with these ratio: (ii) the singlet displacement operator h SD has to be taken into account, at least for the colinear displacement, since h SD ≃ -80 meV.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalous behaviors that are supposed to be related to the presence of the stripes have been observed in the angle-resolved photoemission (ARPES) spectrum as suppressed spectral weight along the (0,0)-(π,π) direction 9 and in the optical conductivity as the enhancement of intensity in the mid-infrared region. 10 These features have been explained by the present authors, by using the exact diagonalization calculation at zero-temperature for a model that includes both the strong electron correlation and the stripes, i.e., a t-J model with an additional potential introduced to stabilize vertical charge stripes.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably the (π, 0) flat band feature which exists in the optimum and underdoped regions does not completely lose its spectral weight even for x = 0.22 (and probably for x = 0.3, see data in Ref. 8 ) where the saddle point is located above E F . Therefore, the spectral weight around (π, 0) appears as a remnant of the "flat band".…”
mentioning
confidence: 98%
“…La 2−x Sr x CuO 4 (LSCO), by virtue of the absence of these effects and the availability of high quality single crystal samples over the entire doping range, provides the opportunity to advance our understanding of the high temperature superconductors. In the underdoped regime, earlier studies have uncovered the presence of two electronic components [8][9][10] , a systematic suppression of the spectral weight near (π/2, π/2) (when compared with that of overdoped samples or BSCCO for data taken under the same conditions), and straight Fermi surface segments near (π,0) of width ∼ π/2 11,12 , which have been interpreted as evidence for electronic inhomogeneities. In the overdoped regime, an electronlike Fermi surface was observed in the high-T c superconductors for the first time 8 , but despite this progress, important problems remain.…”
mentioning
confidence: 99%